WHAT IS SEMANTICS? - Matkarimova, Shokhista; Otaboyeva, Komila Kamoladdin kizi (Innovative Development in Educational Activities, 2024)
Language is the primary source of communication for humans and is used to convey thoughts, feelings, intentions, and desires to others. Knowing a language means to be informed how to make and understand sentences with particular meanings. Semantics is a study of the meaning of lexical items and other parts of language. It is the branch of linguistics that determines how languages organize and express meanings and avoids trying to account for subjective or local meaning. This paper classifies what the semantics is; what it studies; and its types.